Exploring conceptualizations of impact from the perspectives of patient partners working with Canadian health system organizations: a qualitative study - Ivany, Caitlyn (My University, 2025)
Introduction: As the patient partner role, described as the longitudinal and bi-directional involvement of patients, becomes increasingly integrated into health system organizations, it is imperative to understand the impacts of this engagement. The objective of this study is to explore how patient partners conceptualize and aspire to achieve impact through their partnership work, as well as to identify factors that may help to facilitate these impacts. Methods: Guided by Interpretive Description methodology, we conducted 35 semi-structured interviews with patient partners working with health system organizations across Canada. Eligible participants self-identified as a patient, family member, or caregiver with over two years of experience as a patient partner. Participants were recruited through a previous survey, newsletter advertisements, and the research team’s network. Data collection and analysis occurred concurrently in an iterative process and involved staged coding as well as the development of a thematic template consisting of themes and sub-themes related to conceptualizations of impact, aspirations of impact, and factors that facilitate impact. Results: Participants described the impacts of their involvement in three main ways; observable versus perceived impacts, aspirational versus expected impacts, and factors that help to facilitate impact. Observable impacts involved extrinsic concrete changes, while perceived impacts involved a sense of intrinsic validation. Aspirational impacts encompassed changes participants hoped to see, and expected impacts were changes participants anticipated to occur. Lastly, participants highlighted multiple organizational supports that they perceived helped to facilitate impact. Conclusion: Patient partners conceptualized their impact in various ways and commonly discussed observable and perceived impacts in relation to their work within their organization, and broader system change as an aspirational impact. Understanding how patient partners describe and aspire to impact can help organizations optimize impactful partnership work. Future research should explore how organizational staff conceptualize impact to compare these perspectives with those of patient partners.
Keywords: patient engagement; patient partnership; impact conceptualizations; health system organizations; qualitative; patient partner